485Prospective associations between sex hormone-binding globulin and risk of type 2 diabetes. (2nd September 2021) - Woo, Hye Won; Shin, Min-Ho; Choi, Bo Youl; Kim, Mi Kyung
Abstract: Background: Circulating sex hormone–binding globulin levels are inversely associated with insulin resistance. However, epidemiologic evidence on the association of sex hormone-binding globulin (SHBG) and the risk of developing diabetes is limited. This study aimed to evaluate the prospective associations between serum SHBG level and risk of type 2 diabetes (T2D) among adults ≥ 40 years old in the Yangpyeong and Namwon cohort. Methods: A total of 4, 383 (1, 651 men and 2, 732 women) participants who did not have T2D were enrolled. The incidence rate ratio (IRR) was estimated using a modified Poisson regression model with a robust error estimator. During follow-up (27, 146 person-years), 284 T2D cases were newly diagnosed. Results: Significant dose-response inverse associations were observed between serum SHBG (tertiles) and T2D in women, even after controlling for baseline fasting glucose (incidence rate ratio, IRR=0.42, 95% CI = 0.26–0.68, P for trend = <.001 in the highest tertile). Similar significant linear trends were found among menopausal women, and the inverse associations persisted across participant subgroups with diabetes risk profiles. However, there were no significant associations with serum SHBG in men. When we examined the association, except for men with higher levels of hs-CRP (≥ 3 mg/L) and HOMA-IR (≥ 2.5) at baseline, the non-significant associations did not change (IRR=1.45, 95% CI = 0.78–2.70, P for trend=0.167 in the highest tertile). The sex-specific differences in associations between serum SHBG and T2D risk were statistically significant ( P for interaction=0.005). Conclusions: Serum SHBG may be inversely associated with T2D in women, but not in men. Key messages: Circulating SHBG may play different roles in the development of T2D in men and women.